2009
DOI: 10.1093/qjmed/hcp091
|View full text |Cite
|
Sign up to set email alerts
|

Perceived fatigue is comparable between different disease groups

Abstract: Perceived fatigue is similar between patient groups. Increasing scores were not related to simply reaching the maximum threshold in the physical domain. Studies have confirmed a positive-structured approach to symptom management in one fatigue-associated chronic disease, primary biliary cirrhosis, leads to significant improvements in quality of life. We suggest that, with a similar approach, the same might be true in other chronic diseases where moderate fatigue is a significant problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 19 publications
3
24
0
Order By: Relevance
“…14 However, in the NHS in England and Wales only patients with fatigue who fulfil the Fukuda criteria for CFS can currently access specialist fatigue management services.…”
Section: Discussionmentioning
confidence: 99%
“…14 However, in the NHS in England and Wales only patients with fatigue who fulfil the Fukuda criteria for CFS can currently access specialist fatigue management services.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that the fatigue phenotype in a number of chronic diseases, including NAFLD, is comparable between chronic disease groups [32] , which would suggest that interventions applicable to one chronic disease group have the potential to be appropriate generically.…”
Section: Future Studiesmentioning
confidence: 99%
“…Recruitment took place over a period of 13 Data were analysed on an intention-to-treat basis; however, results did not differ from those following per protocol analysis.…”
Section: Study Participantsmentioning
confidence: 99%
“…cancer, rheumatoid arthritis, and multiple sclerosis. Recent evidence suggests similarities in fatigue between different conditions [12,13], though it is unclear which elements of fatigue co-exist. Although physical activity (PA) has been suggested to be appropriate for adults and children with IBD [14,15], patients may raise concerns regarding exerciserelated exacerbation of their symptoms [16].…”
Section: Introductionmentioning
confidence: 99%